PENDIDIKAN ISLAM DALAM KELUARGA (ANALISIS PROBLEMATIKA DAN SOLUSINYA MENURUT PERSPEKTIF MUHAMMAD QURAISH SHIHAB) - Iqbal Anggia Yusuf (HASBUNA : Jurnal Pendidikan Islam, 2023)
The purpose of this study is to analyze the problems that occur in the family, both in terms of the causal factors, the kinds of problems that occur, the characteristics and impacts that arise as a result of the problems in the family. Then provide a solution with the values ​​of Islamic education in the family that must be instilled in the family and analyze what needs to be considered in the education process. This study uses a type of qualitative research with library research (library research). The results of this study reveal that the first thing that must be instilled in children in the family is to get an education by inculcating religious values. The education process given to children can be done in several ways, namely through example, habituation, punishment, reward, and supervision. The education process in the family is carried out by paying attention to aspects such as deliberation, equality, religious motivation and understanding the potentials that exist in the family.